The Expansion of Investor Access to Cultivation Rights: A Socio-Legal Analysis on Agrarian Injustice in Indonesia - Mahfud, Muh.Afif; Djohan, Naufal Hasanuddin (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
Granting cultivation rights for investment interests and ignoring equitable distribution of land ownership can create injustice and agrarian conflict. This is socio-legal research to analyze agrarian conflict through an interdisciplinary lens. All the data obtained is analyzed qualitatively. Based on the study, disharmony is found between the Basic Agrarian Law, which regulates that cultivation rights can only be granted on state land, and the Job Creation Law, which stipulates that cultivation rights can be given over management rights. This overlapping regulation marks a difference in legal policy between the Job Creation Law, which wants to provide convenience to entrepreneurs, and the Basic Agrarian Law, which considers the strategic position of cultivation right so that it is merely granted on state land. This overlapping of legal policy creates legal uncertainty and brings economic implications, creating a higher land ownership inequality between entrepreneurs and the community. Higher landownership inequality brings social implications, namely, higher conflicts in the agrarian sector. This is not according to the principle of protection for weak parties in Indonesian Agrarian Law.